Meeting points: pilgrimage and current Quechua society. Introductory Comments - Allen, Catherine J. (2010)
The text is a mental journey to the festival of Lord of Qoyllurit’i and a presentation of the four papers on this event presented at the Latin American Studies Association (LASA) 2009 meeting that Anthropologica publishes in this section. It highlights the richness of contributions as they provide information, ideas, and new interpretations, and shows the strength and intensity of the experience that they evoke.